The Ku Klux Klan in the heartland - Madison, James H. (Indiana University Press, 2020)
"Who is an American?" asked the Ku Klux Klan. It is a question that echoes as loudly today as it did in the early twentieth century. But who were the Klan? Were they "hillbillies, the Great Unteachables" as one journalist put it? It would be comforting to think so, but how then did they become one of the most powerful political forces in our nation's history? In The Ku Klux Klan in the Heartland, renowned historian James H. Madison details the creation and reign of the infamous organization. Through the prism of their operations in Indiana and the Midwest, Madison explores the Klan's roots in respectable white protestant society. Convinced that America was heading in the wrong direction because of undesirable "un-American" elements, Klan members did not see themselves as bigoted racist extremists but as good Christian patriots joining proudly together in a righteous moral crusade. The Ku Klux Klan in the Heartland offers a detailed history of this notorious organization and examines how, through its use of intimidation, violence, and the ballot box, the activities of Klan in the 1920s have continued implications for Americamadison today"--